Educational method to investigarte the Relationship between Organizational Climate and Deviant Behaviors with the Mediation of Job Alienation Variable (Case Study: National Iranian Copper Industries Company) - Amin Farahbakhsh, Amin; Salajeghe, Sanjar; Ziaaddini , Mohammad (Revista Tempos e Espaços em Educação, 2020)
Regarding the size and dispersion of the complex of copper factories in Iran and the high annual costs of preventing employees' strikes and also reducing deviant behaviors, and the existence of appropriate organizational climate, the aim of the present article is to find an educational method to investigate the relationship between organizational climate and deviant behaviors with the mediation of job alienation variable. This research is applied in terms of purpose, and in terms of nature, it is descriptive-correlation and it was conducted in field method. The statistical population of the research was the employees of the National Iranian Copper Industries Company (1010 people) whom are tried to educate this method. The sample size was calculated using the Cochran formula and 278 individuals were selected by simple random sampling. For data collection, the questionnaire of the organizational climate of Sasman and (Dalal, 2005), the adapted questionnaire of deviant behaviors of (Yoon Goo et al, 2013), and the questionnaire of job alienation of (Rahimi et al, 2016) were used. The reliability of the questionnaires in this research was respectively calculated as 0.851, 0.724, and 0.757. For data analysis, the Pearson correlation coefficient, multiple regression and, path analysis tests were used. The results indicated a positive and significant relationship between organizational climate and deviant behaviors, a negative and significant relationship between job alienation and deviant behaviors, and also explaining about 45% of deviant behaviors by organizational climate variables. It can be said that managers' attention to increase positive organizational climate and to decrease employees' job alienation can lead to further reduction of employees' deviant behaviors.